Comparative in-vitro degradation of hyaluronic acids exposed to different hyaluronidase enzymes - Marcelo Germani; Márcia V.G.B. de Queiroz; Mariana Yuri de França Shimizu; Thiago Gomes Teixeira; Victor Rogerio; Gabriela Giro; Victor R.M. Munoz-Lora (Journal of Oral Biology and Craniofacial Research)
Objectives: This study aimed to compare the in-vitro behavior of four Hyaluronic acid (HA) gels when exposed to two different hyaluronidase (HSE) formulations. Methods: Four commercially available HA were used: Lyft (Lt; Restylane, Galderma, Sweden), Voluma (Vol; Allergan, AbbVie, USA), UltraDeep (UDe; Rennova, Innovapharma, Brazil), and Subskin (Skn; Perfectha, Sinclair, France). The gels were divided into two groups, with seven aliquots (0.1 mL per aliquot) for each group deposited on a glass plate. A millimeter ruler was positioned behind the plate to measure the gel height. Each aliquot received 100 UTR of one of two HSE formulations. After 2 min, each aliquot was mixed using a 22G needle and left to sit for additional 2 min. Results: Partial and final degradation of the products were obtained through photographic analysis. The final percentage of degradation exhibited significant differences among HA gels (P < 0.001). The results revealed higher degradation in Lt, moderate degradation in UDe, and lower degradation in Vol and Skn. Comparisons of HSE formulations showed no significant differences among them (P = 0.881). Moreover, there was a noticeable degradation after mixing (P < 0.001). Conclusions: Within the limits of this study, it can be suggested that Lt exhibits the higher degradation among the experimented gels. Furthermore, differences among HSE formulations do not appear to significantly impact HA degradation, while the mixing movement of HSE and HA seems to influence the degradation rate. These findings may help guide clinical decisions regarding the use of hyaluronidase in managing HA filler complications or adjustments.